Perspektif Mahasiswa Terhadap Judi Online di Indonesia: Wujud Kesadaran Hukum dan Etika Digital Warga Negara - Hanum, Fathikah Fauziah; Fathurrahman, Ali Masykur; Kusdarini, Eny; Febiantoni, Fungki; Aziz, Sulthon Abdul (Department of Pancasila and Civic Education, Universitas Negeri Medan, 2025)
This study analyzes students' perspectives on online gambling regulations in Indonesia. It focuses on understanding students who are part of the younger generation and actively engage in the digital world to assess legal awareness and digital ethics among citizens. The research employs a quantitative descriptive method using a cross-sectional approach and was conducted at a university in Yogyakarta. Stratified random sampling was used for sample selection, and data were collected through a questionnaire, which served as a non-test instrument. The data analysis technique utilized was quantitative data analysis. The results indicated that students' knowledge and understanding of online gambling regulations fell into the